2019
DOI: 10.2147/idr.s190859
|View full text |Cite
|
Sign up to set email alerts
|

<p>Procalcitonin-guided antibiotic discontinuation in ventilator-associated pneumonia: a prospective observational study</p>

Abstract: Background: Procalcitonin (PCT), an important biomarker, can be used for the guidance of antibiotic therapy in respiratory infection. However, it has been a problem that some patients might need antibiotic therapy restart because of infection recurrence after antibiotic discontinuation. To date, there are very few literature on the study of risk factors accounting for infection recurrence. Purpose of this clinical study: 1) To study on antibiotic discontinuation in ventilator-associated pneumonia (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
2
1
0
1
Order By: Relevance
“…Our findings indicate that discontinuation of antibiotic treatment based on PCT levels was associated with high recurrent infection rates. This finding is similar to that of a recent trial conducted in 2019 that revealed a recurrent infection rate of 32.9% after discontinuation of antibiotic within 7 days [ 17 ]. Bouadma et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings indicate that discontinuation of antibiotic treatment based on PCT levels was associated with high recurrent infection rates. This finding is similar to that of a recent trial conducted in 2019 that revealed a recurrent infection rate of 32.9% after discontinuation of antibiotic within 7 days [ 17 ]. Bouadma et al .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicate that discontinuation of antibiotic treatment based on PCT levels was associated with high recurrent infection rates. This finding is similar to that of a recent trial conducted in 2019 that revealed a recurrent infection rate of 32.9% after discontinuation of antibiotic within 7 days [17]. Bouadma et al revealed in the PRORATA trial 2010 that the incidence of superinfection in the PCT group was 34.9% of 307 patients in the PCT arm and 30.9% of the 314 patients in the non-PCT arm [18].…”
Section: P-valuesupporting
confidence: 86%
“…Moreover, the bacteriological test lasts for a long time, delaying the treatment (9). It was found in previous clinical practice that PCT can be used to diagnose early potential infection in patients with VAP more accurately (10). PCT is produced by thyroid C cells and possesses no physiological activity, so its content in plasma is extremely low under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Em resposta à agressão bacteriana, o valor de PCT tende a aumentar rapidamente, tendo seu pico plasmático máximo após 12 horas, com meia-vida de 36 horas após o fim do estímulo (CORBACHO et al, 2019). Os resultados do estudo de Tang Quanto ao prognóstico desses pacientes, nenhuma mortalidade ocorreu em 28 dias em nenhum dos grupos (Wang et al, 2019). Seguindo essa mesma linha, Z.…”
Section: Desenvolvimentounclassified